2022
DOI: 10.1108/bfj-02-2022-0095
|View full text |Cite
|
Sign up to set email alerts
|

Food delivery, ghost kitchens and virtual restaurants: temporary or long-lasting game changers?

Abstract: PurposeThis paper aims to investigate the phenomenon of online food purchasing in Italy and, specifically, Italian consumers' future intentions to use these services even after the end of the COVID-19 emergency. To this purpose, to understand if these phenomena are robust enough to represent irreversible and well-established trends, in the present study, consumers’ Behavioural Intention was investigated.Design/methodology/approachA theoretical framework based on a preliminary literature analysis on the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In addition, behavioural intention towards OFODSs and perceived trust considerably influenced the use of these apps. According to Nigro et al . (2022), convenience, variety of food and time savings influence behavioural intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, behavioural intention towards OFODSs and perceived trust considerably influenced the use of these apps. According to Nigro et al . (2022), convenience, variety of food and time savings influence behavioural intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, behavioural intention towards OFODSs and perceived trust considerably influenced the use of these apps. According to Nigro et al (2022), convenience, variety of food and time savings influence behavioural intentions. Al revealed that hygiene, subjective norms, attitudes and behavioural control were related to behavioural and continuance intentions to use mobile food delivery apps.…”
Section: Ofods Quality and Customer Expectationsmentioning
confidence: 99%
“…In recent years, the food delivery market, which includes services that deliver food ordered through very different channels for direct consumption, has gained popularity worldwide. This phenomenon refers to the restaurant-to-consumer delivery segment, which includes food delivery made directly by restaurants for orders placed through platforms (platform-to-consumer delivery), as well as through restaurants' websites, apps and social media, or by phone/email (Nigro et al, 2022).…”
Section: Dark Kitchens -Literature Review and Contextual Backgroundmentioning
confidence: 99%
“…For the last two decades, the field of technologies Information and Communication (TIC) advanced for opening a break-grounding change in business and management (Kraus et al, 2022;Lau and H€ oyng, 2023), also in channels of distribution in tourism and leisure industry (Buhalis and Law, 2008;Law et al, 2014;Martin-Fuentes and Mellinas, 2018). Other areas experiencing changes in TIC, such as restaurant reservation, evolved similarly to bring a revolution to the tourism and food sectors (Ye et al, 2011;Law et al, 2014;Thompson, 2015;Quaglione et al, 2020;Nazmi et al, 2022;Nigro et al, 2023), via product acquisition for introducing channels of distribution in the digital space (Xiang et al, 2015;Angeloni and Rossi, 2021), and via using multiple devices (Palau-Saumell et al, 2019;Kamboj and Joshi, 2021;Zanetta et al, 2021;Sharma et al, 2023). TIC areas being in the midst of changes, is happening for users planning their travelling, where users go ahead and make public a visualisation of the This paper has been developed under an art.…”
Section: Introductionmentioning
confidence: 99%
“…, 2011; Law et al ., 2014; Thompson, 2015; Quaglione et al. , 2020; Nazmi et al ., 2022; Nigro et al. , 2023), via product acquisition for introducing channels of distribution in the digital space (Xiang et al ., 2015; Angeloni and Rossi, 2021), and via using multiple devices (Palau-Saumell et al.…”
Section: Introductionmentioning
confidence: 99%